2017
DOI: 10.2139/ssrn.2977074
|View full text |Cite
|
Sign up to set email alerts
|

Government Expropriation Increases Economic Growth and Racial Inequality: Evidence from Eminent Domain

Abstract: Is it justified for states to appropriate private property rights? If so, should governments expropriate or regulate? We test three conventional views: insecure property rights cause underinvestment, moral hazard cause overinvestment, or public use cause economic growth. We embed these mechanisms in a model and measure them using the random assignment of U.S. federal court judges setting geographicallylocal precedent. For a half-century, racial minority Democrats were more likely to strike down government appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…The redistributive effect I observe is therefore not only with regard to transfers from Palestinians to Jews, it is also potentially with regard to transfers from the poor to the rich. As already hinted and as previously observed in the literature, these two stories are not independent (Somin 2015; Becher 2014; Chen and Yeh 2012; Carpenter and Ross 2009) and this is yet another case for the effects of intersectionality and the need to provide public policy solutions to them (Hankivsky and Cormier 2011; Crenshaw 1988).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The redistributive effect I observe is therefore not only with regard to transfers from Palestinians to Jews, it is also potentially with regard to transfers from the poor to the rich. As already hinted and as previously observed in the literature, these two stories are not independent (Somin 2015; Becher 2014; Chen and Yeh 2012; Carpenter and Ross 2009) and this is yet another case for the effects of intersectionality and the need to provide public policy solutions to them (Hankivsky and Cormier 2011; Crenshaw 1988).…”
Section: Discussionmentioning
confidence: 83%
“…In an important contribution, Chen and Yeh (2012) examined the effects of pro-taking court precedents. They reported that court decisions that expanded the government’s power of expropriation spurred economic growth and property prices by 0.2 percent, but reduced racial minorities’ home ownership and employment by 0.5 percent and 0.3 percent, respectively.…”
Section: Distribution Of the Taking Burdens And Benefits Across Polit...mentioning
confidence: 99%
“…Table 8 lists a few. The data is then merged with judge biographies, both from the Federal Judiciary Center as well as separate data collection from newspaper articles (Chen and Yeh 2014a).…”
Section: Machine Learning and Judicial Indifferencementioning
confidence: 99%